Adequacy and quality of immunization data in a comprehensive electronic health record system. - Keny, Aggrey; Biondich, Paul; Grannis, Shaun; Were, Martin C. (Journal of Health Informatics in Africa, 2013)
Background and Purpose: Timely, simultaneous and combined vaccination is important to protect children from common infectious diseases. In a large health care delivery system in Western Kenya, we examined the adequacy and quality of data within the electronic health record (EHR) to assess the feasibility of developing a clinical decision support system to improve childhood vaccination uptake and coverage.Methods: The study evaluated vaccination information collected and stored in an EHR between 2006 and 2012 involving 23,270 children. Encounters for 10,299 children lacked immunization information and were excluded. Results: Documentation of vaccination coverage and timeliness is rendered in Kaplan–Meier time-to-event plots. Vaccination coverage at the end of one year ranges from 60% to 90% for all vaccines assessed individually that are part of the Kenya Expanded Program on Immunization (KEPI). Timely documentation of vaccination is low, with 52.8 weeks (95% CI: 52.1, 53.5) for measles vaccine and 29.2 weeks (95% CI: 28.5, 29.8) for the Bacillus Calmette–Guérin (BCG) vaccine.  Complete vaccine observations were recorded in 16% of the encounters. Combination and simultaneous vaccine administration had high congruence and consistency.Conclusion: A clinical decision support system that generates reminders to clinicians and caretakers of children would optimize vaccination uptake and improve overall immunization coverage. To achieve this, immunization data in the EHR must be timely, complete and consistent. Assessed vaccination timeliness is low, despite high coverage. Vaccine observations are often incomplete. There is need to improve the data collection process to achieve data quality levels that can adequately support a clinical decision support system.Keywords: Vaccination, Electronic health records, Developing countries, Data quality